PHENOTYPIC VARIABILITY EVALUATION OF WHEAT VARIETIES FROM THE SUCEAVA GENE BANK COLLECTION - Tiberiu Emilian SÂRBU; Iulian GABUR; Dănuț Petru SIMIONIUC; Daniela Domnica PLĂCINTĂ; Danela MURARIU; Violeta SIMIONIUC (Journal of Applied Life Sciences and Environment)
The intensity of selection, inadvertent pathways of domestication, and the influence of climate change collectively amplify the frequency of detrimental alleles. This phenomenon, in turn, triggers genetic drift, leading to an in-advertent decline in the diversity of plant genetic resources. Genetic variability is of utmost importance for a species’ adaptability and overall fitness. Our investigation centres on Triticum germplasm within the agroclimatic conditions of the Suceava Gene Bank, encompassing 2021–2022 field trials. Comprehensive morphophysiological characterisation was conducted across 200 cultivated varieties, spanning three Triticum species (T. aestivum, T. turgidum and T. monococcum). Initially, the data underwent meticulous processing involving the computation of amplitude of variation, variance (s2), standard deviation (√s), and coefficients of variation (s%) for three pivotal agronomical traits: plant height, spikelets per spike, and total seeds per spike. Furthermore, an extensive cluster analysis was performed, encompassing multiple vital plant descriptors. The findings unveiled a remarkable dispersion of data, with standard deviation, amplitude of variation, and coefficient of variation collectively indicating substantial variability among the cultivated varieties. Within the same population, an intriguing observation emerged; of the 200 genotypes analysed, 83 exhibited immunity to Septoria tritici. Delving deeper into the statistical analysis, we identified two primary clusters within the population. Overall, a significant proportion of this germplasm showcased elevated phenotype scores, rendering them well-suited for further exploration as foundational material in pre-breeding initiatives.